Effect of tetrastarch (hydroxyethyl starch 130/0.4) on plasma creatinine concentration in cats: a retrospective analysis (2010–2015). Issue 10 (October 2017) - Yozova, Ivayla D; Howard, Judith; Adamik, Katja N
Objectives: The objective was to determine survival and changes in creatinine concentrations after administration of 6% tetrastarch (hydroxyethyl starch [HES] 130/0.4) vs crystalloids in critically ill cats. Methods: The medical records were reviewed for cats admitted to the intensive care unit with at least two plasma creatinine measurements and initial concentrations not exceeding the upper reference interval. Cats were excluded if they had received HES prior to admission or if they had received fluid therapy for <24 h between initial and subsequent measurements. Changes in creatinine concentrations were evaluated as the percentage change from initial values to the maximum subsequent measurements. Cats receiving only crystalloids were assigned to the crystalloid group; cats receiving only HES or HES and crystalloids were assigned to the HES group. Results: Ninety-three cats were included in the study (62 in the crystalloid group, 31 in the HES group). The total median cumulative HES dose was 94 ml/kg (range 26–422 ml/kg) and 24 ml/kg/day (range 16–42 ml/kg/day). No difference was detected between the groups for age, sex, body weight or mortality. The HES group had a significantly longer length of hospitalisation ( P = 0.012), lower albumin concentrations ( P <0.001), higher Acute Patient Physiologic and Laboratory Evaluation scores ( P = 0.037) and higher incidence of systemic inflammatory response syndrome ( P = 0.009) and sepsis ( P = 0.013). There was no significant difference in initial, maximum or maximum change in creatinine concentrations between the groups. Moreover, there was no significant difference in maximum change in creatinine concentrations in the subgroups of cats with systemic inflammatory response syndrome or sepsis. Conclusions and relevance: In this population of cats, the administration of HES did not result in a significantly greater increase in creatinine from values measured on admission or higher mortality compared with administration of crystalloids. Further prospective studies are needed to assess both safety and efficacy of HES in cats before recommendations can be made.